2022
DOI: 10.1002/chem.202200249
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis for a Wide Variety of Patellamide Derivatives and Phosphatase Activity of Copper‐Patellamide Complexes

Abstract: Copper complexes of patellamides have shown catalytic activity in a variety of reactions but their biological function remains unknown. There are significant differences between the natural macrocycles and synthetic analogues in the various catalytic activities. It therefore is essential to be able to perform in vivo and ex vivo reference measurements with the natural patellamide macrocycles, very similar derivatives and a large range of synthetic analogues. The preparative method described allows for a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…First, the introduction of L-Car molecules enhances the affinity between CMNC and the phosphate ester substrates through hydrogen bonding while facilitating proton transfer during dephosphorylation. This proton-transfer relay system is initially initiated by the imidazole group of L-Car , and can supply and withdraw protons whenever required. Second, the imidazole group of L-Car acts as an electrophilic/electrostatic activator and a general base .…”
Section: Resultsmentioning
confidence: 99%
“…First, the introduction of L-Car molecules enhances the affinity between CMNC and the phosphate ester substrates through hydrogen bonding while facilitating proton transfer during dephosphorylation. This proton-transfer relay system is initially initiated by the imidazole group of L-Car , and can supply and withdraw protons whenever required. Second, the imidazole group of L-Car acts as an electrophilic/electrostatic activator and a general base .…”
Section: Resultsmentioning
confidence: 99%
“…This was not expected on the basis of the experimental data because these included only a limited range of cyclic peptides. [22] Interestingly, the importance of electronic effects is in contrast to observations derived from phosphoester hydrolysis catalyzed by dicopper-(II)complexes of patellamide derivatives, where in a similar computational study the reactivities were shown to be primarily dependent on the stereochemistry, [14] and it appears that this is due to the differing steric demand of the two substrates.…”
Section: Reactivity In Dependence Of the Orientation Of The Side-chai...mentioning
confidence: 94%
“…On the other hand, their natural role is unknown; thus, accessing these NPs can open future lines of research towards their role in nature. Multiple cyanobactins have been synthesized, for example, bistratamide D, [5] trunkamide A, [6] aerucyclamide B, [7] patellamide A and its derivatives, [4,8] among others, however, several cyanobactins have not been accessed synthetically yet (Figure 1A). Herein, we report the first total synthesis of balgacyclamide B cyanobactin.…”
Section: Introductionmentioning
confidence: 99%